2016
DOI: 10.1124/mol.116.104752
|View full text |Cite
|
Sign up to set email alerts
|

The Histamine H3Receptor: Structure, Pharmacology, and Function

Abstract: Among the four G protein-coupled receptors (H-H) identified as mediators of the biologic effects of histamine, the H receptor (HR) is distinguished for its almost exclusive expression in the nervous system and the large variety of isoforms generated by alternative splicing of the corresponding mRNA. Additionally, it exhibits dual functionality as autoreceptor and heteroreceptor, and this enables HRs to modulate the histaminergic and other neurotransmitter systems. The cloning of the HR cDNA in 1999 by Lovenber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
136
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(150 citation statements)
references
References 247 publications
1
136
0
2
Order By: Relevance
“…The full length human H 1 , H 2 , H 3 , and H 4 receptors are composed of 487, 359, 445, and 390 amino acids, respectively (Simons 2004). H 4 receptor has 40% homology with the H 3 receptor, and was identified based on differences in tissue distribution and binding affinity (Nakamura et al 2000). Liu et al (2001) identified 35% homology between the H 4 receptor and the H 3 receptor (Table 1).…”
Section: Histamine In the Context Of Atopic Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The full length human H 1 , H 2 , H 3 , and H 4 receptors are composed of 487, 359, 445, and 390 amino acids, respectively (Simons 2004). H 4 receptor has 40% homology with the H 3 receptor, and was identified based on differences in tissue distribution and binding affinity (Nakamura et al 2000). Liu et al (2001) identified 35% homology between the H 4 receptor and the H 3 receptor (Table 1).…”
Section: Histamine In the Context Of Atopic Diseasementioning
confidence: 99%
“…Acting through the presynaptic H 3 receptor, histamine regulates its own release (negative feedback) as well as the release of other neurotransmitters such as noradrenaline, dopamine, serotonin, acetylcholine, and gammaamino-butyric acid. In the lower airways, H 3 receptors are located on postganglionic cholinergic nerves and counteracts bronchoconstriction, through stimulation of phospholipase A2 and subsequent enhanced release of endothelium-derived relaxing factor in guinea pigs (Barnes 1991;Burgaud and Oudart 1993;Nieto-Alamilla et al 2016). In the upper airways, histamine may play a role in nasal congestion through its activity at H 3 receptors.…”
Section: Histamine Receptor Expression and Functionmentioning
confidence: 99%
“…These receptors are mainly located in different areas of CNS regulating the release of histamine and other neurotransmitter such as acetylcholine and dopamine through a negative feedback mechanism. The H 3 R belongs to the superfamily of G protein‐coupled receptors and is coupled to the G i/o class of G proteins, leading to inhibition of the adenylyl cyclase with the subsequent decrease in the level of cAMP, among other actions (Nieto‐Alamilla, Marquez‐Gomez, Garcia‐Galvez, Morales‐Figueroa, & Arias‐Montano, ). There are lines of evidence indicating that H 3 R blockade enhances acetylcholine release, thereby leading to improved cognitive and behavioral symptoms (Brioni, Esbenshade, Garrison, Bitner, & Cowart, ; Medhurst et al, ; Raddatz, Tao, & Hudkins, ; Sadek, Saad, Sadeq, Jalal, & Stark, ).…”
Section: Introductionmentioning
confidence: 99%
“…H 3 R antagonists have been investigated as potential treatments for several CNS disorders, including sleep disorders, schizophrenia, epilepsy, attention deficit, hyperactivity disorder, and even obesity. There is also potential for H 3 R antagonists to have effects in neurodegenerative disorders such as Alzheimer's disease, Parkinson's disease, and Huntington's chorea . Recently, a H 3 R antagonist (pitolisant) has been approved for the maintenance of wakefulness in patients with narcolepsy .…”
Section: Introductionmentioning
confidence: 99%